Smartphone as Polymedia for Mothers During Pandemic - Snezana Swasti Brodjonegoro (FISIP Universitas Atma Jaya Yogyakarta, 2023)
Drawing from the notion of smartphones as polymedia, this study seeks to investigate how working mothers use smartphones to navigate multiple roles during the COVID-19 pandemic. Smartphones become an essential device for working mothers as it allows them to manage different relationships and tasks that are imperative to their various roles. This study employs a phenomenology approach, using interviews with eight working mothers in six cities in Indonesia. This study brings into light three relational dynamics of smartphones as polymedia that helped them navigate the change of the COVID-19 pandemic, namely entertainment, empowerment, and support.